A biomaterial doped with LaB6 nanoparticles as photothermal media for enhancing biofilm growth and hydrogen production in photosynthetic bacteria. (2nd March 2017) - Li, Yishan; Zhong, Nianbing; Liao, Qiang; Fu, Qian; Huang, Yun; Zhu, Xun; Li, Qiaoliang
Abstract: A novel photothermal biomaterial, designated GeO2 -SiO2 -Chitosan-Medium-LaB6 (GSCML), was prepared to improve photosynthetic bacteria (PSB) biofilm development and hydrogen production performance. This biomaterial employed spectral beam splitting technology to increase the overall utilization of the incident light spectrum, which LaB6 nanoparticles (NPs) mainly absorb light at approximately 380–510 and 660–780 nm and convert it into heat energy; the transmit light is around 590 nm for PSB growth. The temperature increased, and the luminous intensity of the light transmitted through the prepared biomaterial are controlled by adjusting the LaB6 NPs' content. The average biofilm growth rate and hydrogen production rate of the biofilm on the created biomaterial were 0.05 mg/cm 2 /day and 2.92 mmol/h/m 2, which were 3.4 and 4.1 times higher than those of the glass slide, respectively. The properties of the GSCML biomaterial provide advantages for applications in immobilized cell technologies and photobioreactors. Highlights: A novel photothermal biomaterial doped with LaB6 NPs named as GSCML was prepared. The proposed biomaterial can improve PSB biofilm development and H2 production. The biofilm growth rate and H2 production rate were greatly enhanced. Temperature increase and light intensity of light transmitted through the biomaterial can be controlled. The biomaterial is applicable for large-scale PSB immobilization and H2 production.